Secondary School Students' STEM Education Anxiety: The Role of Teachers’ Teaching Self-Efficacy Beliefs and Outcome Expectancy Beliefs - Khan, Md. Iftakharul Islam; Rahman, Jakia (Psikoislamika: Jurnal Psikologi Islam, 2024)
STEM education is a method of instruction that allows students to apply concepts from science, technology, engineering, and mathematics to a variety of contexts, preparing students for the real world by teaching them to respond to change and equipping them with skills such as critical thinking, problem-solving, and creativity and STEM anxiety is the worry, avoidance, or fear of studying science or mathematics. The study sought to investigate the relationship between students' STEM education anxiety and instructors' self-efficacy and expectancy-value beliefs, as there has been little empirical research into the impact of such factors on anxiety. This study examined the association between Bangladeshi secondary school students' STEM education anxiety and their teachers' own teaching efficacy and teaching outcome expectancy beliefs. The convenience sampling method was used to collect responses from 165 secondary school pupils and their 50 teachers. Surveys were administered to assess teachers' self-efficacy and outcome expectations, as well as students' STEM education anxiety. The analyses included mean, standard deviation, correlation, independent sample t-test, and multiple regression analysis. Teachers’ teaching efficacy and beliefs (PTEB) and teaching outcome expectancy beliefs (TOEB) were negatively correlated with students’ STEM education anxiety. The study highlights how teachers' self-efficacy and outcome expectations affect students' STEM-related anxiety.